Mastectomy – literature review - Trojan, Sara; Błaszczyk, Agnieszka; Fussek-Styga, Urszula; Kwieciński, Jakub; Miszuda, Sławomir; Basiaga, Bartosz; Bednarz, Krzysztof; Szwedkowicz, Agata; Leśniak, Marek; Heluszka, Jakub (Quality in Sport, 2023)
The dominant approach in the fight against breast cancer is mastectomy. Surgical operations include diagnostic, therapeutic, palliative and reconstructive procedures. The decision as to the procedure depends on the type, location and advancement of the tumor, as well as on the preferences of the patients, the skills of the operator and the availability of methods at a given centre. It is worth noting that with the increasing number of patients, there have also been significant advances in treatment, the surgical techniques used, and consequently the quality of life index has also increased. Nowadays, clinicians' attention is focused not only on the elimination of the cancer, but also on the best possible cosmetic effect of the treatment. In breast cancer, the approach to the patient should be multidisciplinary, because mastectomy and its complications affect the patient's appearance after surgery, as well as psychological aspects, changing self-perception and pain complaints.